Effect of different stocking densities on survival and growth of sugpo (Penaeus monodon Fabricius in a milkfish-rearing pond - Primavera, J.H; Apud, F.; Usigan C. (1976)
Employing a direct stocking monoculture method, postlarval P. monodon were stocked in 8 compartments of a shallow milkfish rearing pond at densities of 1, 2, 3 and 4/sq m with replicates. Feeding was exclusively natural (microbenthic lablab and plankton); Chanos fingerlings were later introduced to control excessive growth of lablab. Measurements of temperature, DO, pH, salinity and alkalinity were taken daily; stock sampling of length and weight was done every 30 days. Halfway through the culture period, the nylon net separating the compartments was accidentally lifted thereby invalidating data for 5 of the compartments. The prawns were harvested after 5.5 months. Survival was approximately the same for all stocking rates (51.76% at 4/sq m; 50.20% at 2/sq m; 42.54% at 1/sq m and 49.75% for the five remaining compartments treated as one). Growth rates are less conclusive due to the paucity of data. Effects of such physiochemical conditions as high and shallow depth are discussed.